Association between the dietary index for gut microbiota and female infertility: a cross-sectional study of NHANES 2013–2018 - Zhang, Xiaoyan; Wu, Liangzhi; Li, Haiyan; Zhang, Shuyao; Hua, Wenfeng (Frontiers in Nutrition, 2025)
BackgroundInfertility poses a substantial societal and economic burden; however, current preventive strategies are limited. Recently, the relationship between gut microbiota and infertility has garnered increasing attention. The dietary index for gut microbiota (DI-GM) is a new index that reflects the diversity of the gut microbiota. However, its association with female infertility remains unclear.MethodsThis cross-sectional study included 3,053 women aged 18–45 years from the National Health and Nutrition Examination Survey (NHANES) database between 2013 and 2018. Infertility was defined based on responses to a questionnaire on reproductive health. The DI-GM score was calculated by averaging the intake from two 24-h dietary recall interviews. Weighted multivariable logistic regression, restricted cubic splines (RCS), and subgroup analyses were used to investigate the association between DI-GM and female infertility.ResultsBased on self-reported data, 370 participants (12.12%) were classified as infertile. A higher proportion of participants with lower DI-GM scores experienced infertility. Multivariable logistic regression analysis indicated a negative association between DI-GM and the risk of female infertility, regardless of whether the independent variable was analyzed as a continuous variable or in quartiles in the fully adjusted model (Model 3, continuous variable: OR = 0.89, 95% confidence interval (CI): 0.80–0.98, p = 0.025; Q4 vs. Q1: OR = 0.63, 95% CI = 0.42–0.94, p = 0.032, p for trend = 0.013). The RCS curves demonstrated a non-linear relationship between the DI-GM scores and infertility risk. Subsequent subgroup analyses corroborated the robustness of these findings.ConclusionThese findings suggest a non-linear relationship between DI-GM and the risk of infertility in females, with lower DI-GM scores associated with a higher risk of infertility.